FACTOR ANALYSIS OF THE STATE OF SURFACE WATERS IN THE DNIPRO BASIN - Shara, S.; Tkachenko, I. (Municipal economy of cities. Series: «Economy science», 2025)
Monitoring wind-wave erosion (abrasion) of the shores of the Dnipro basin is crucial, as continuous erosion gradually causes shoreline retreat. This process can lead to land loss and pose a threat to infrastructure. Abrasion landforms such as cliffs, escarpments, marine terraces, niches, and platforms may develop. Shoreline erosion increases the number of suspended particles in the water, affecting water quality and ecosystems by raising turbidity. Geoinformation monitoring of surface waters is an essential area of scientific research that combines the use of Geographic Information Systems (GIS) and remote sensing (RS) to assess and manage water resource quality. Water monitoring in Ukraine is regulated by the Water Code, along with various legislative acts and government resolutions. Using satellite data visualization on the Giovanni portal, we analyzed the correlation between water temperature in the Kremenchuk Reservoir and chlorophyll concentration (an indicator of the number of photosynthesizing microorganisms in the aquatic environment, including algal blooms). The dependence of these indicators is high in the southern part of the reservoir, reaching 0.6–0.8, where both temperature and chlorophyll concentration are significantly elevated. The average correlation coefficient for the entire Kremenchuk Reservoir is 0.40. To determine the contours of the reservoir’s shoreline, we used images from July 2024 (Sentinel-2) and July 1994 (Landsat 4-5) obtained via the EO Browser. These images were used to forecast and characterize shoreline changes. By processing the 2024 and 1994 images and displaying the Normalized Difference Water Index (NDWI), we calculated the reservoir’s surface area and found that over 30 years, it has decreased by 9,086.03 hectares. To determine the depth of the Kremenchuk Reservoir, we downloaded data from the GEBCO Gridded Bathymetry Data 2023. Based on these data, a 3D model of the reservoir bed was constructed using QGIS and Autodesk Civil 3D, displaying contour lines and characteristic elevation points of the reservoir bottom. The most accurate and appropriate method for bathymetric surveying is airborne LiDAR scanning, which performs precise scanning and mapping. Continuous monitoring of water bodies using remote sensing methods, especially in the context of environmental aggression, war, and ongoing violations by economic entities, enables prompt responses to environmental violations and challenges.